2018
DOI: 10.18267/j.efaj.185
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Corporate Income Tax on R&D of Multinational Entities: An Impact Analysis of Separate Taxation and CCCTB

Abstract: The significant contribution of R&D to economic development and sustainability has been shown by various studies. Therefore, governments offer different fiscal instruments to attract R&D, especially regarding multinational entities (MNEs). One of the fiscal instruments are tax incentives for R&D. Furthermore, the EU has been working on the switch from Separate Taxation (ST) to Common Consolidated Corporate Tax Base (CCCTB) for longer than a decade, which will lead to harmonized R&D tax allowances, however with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Scholars have suggested that short-term losses of the total corporate income tax revenue are between 5 and 10% (Cobham and Janský, 2018;Crivelli et al, 2016). In addition, many authors have argued that the status quo favours multinational companies over purely domestic companies, resulting in the overall tax burden borne by multinational and purely domestic companies being significantly different (e.g., Solilová and Nerudová, 2019;Hulya and Hodžić, 2017;Hansson et al, 2017;Egger et al, 2010;Azémar and Corcos, 2009). Reflecting the digitalized context, the European Commission 2 estimated the difference in the tax burden borne by traditional and digital multinational companies.…”
Section: Introductionmentioning
confidence: 99%
“…Scholars have suggested that short-term losses of the total corporate income tax revenue are between 5 and 10% (Cobham and Janský, 2018;Crivelli et al, 2016). In addition, many authors have argued that the status quo favours multinational companies over purely domestic companies, resulting in the overall tax burden borne by multinational and purely domestic companies being significantly different (e.g., Solilová and Nerudová, 2019;Hulya and Hodžić, 2017;Hansson et al, 2017;Egger et al, 2010;Azémar and Corcos, 2009). Reflecting the digitalized context, the European Commission 2 estimated the difference in the tax burden borne by traditional and digital multinational companies.…”
Section: Introductionmentioning
confidence: 99%